1997
DOI: 10.1161/01.hyp.29.3.751
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers Blunt Postural Cutaneous Vasoconstriction in Hypertensive Patients

Abstract: The aim of this work was to test whether calcium channel blockers interfere with skin vasoconstrictor reflexes that minimize postural increases in capillary pressure and avoid fluid extravasation and eventually subcutaneous edema. Studies were conducted in 23 untreated mild to moderate essential hypertensives; drugs, either calcium channel blockers or not, were given for 2 weeks according to a crossover, sequence-randomized design. Skin blood flow was measured by laser Doppler flowmetry in two skin areas: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…That consistent behaviour suggests a permissive role of gravitational factors in promoting and favouring oedema formation, and allows to postulate an interference of CCBs with postural vasoconstriction, similar with other vasoconstrictor responses [25][26][27] dependent on extracellular calcium influx into vascular smooth muscle cells. 28 In agreement with this expectation, two DHP CCBs such as nifedipine and amlodipine, 29,30 as well as the unrelated phenylalkylamine derivative verapamil, 29 were able to reduce postural vasoconstriction at the dorsum of the foot 24,31 (Figure 3), a result in agreement with several other reports [32][33][34] (Table 1). Attenuation of postural vasoconstriction was probably the result of 35 Furthermore, non-CCB vasodilators, such as doxazosin, losartan and captopril (Figure 3), left postural vasoconstriction undisturbed in spite of a degree of microvascular dilation comparable to that induced by calcium channel blocking drugs.…”
Section: Ccbs Antagonise Postural Vasoconstrictionsupporting
confidence: 83%
See 2 more Smart Citations
“…That consistent behaviour suggests a permissive role of gravitational factors in promoting and favouring oedema formation, and allows to postulate an interference of CCBs with postural vasoconstriction, similar with other vasoconstrictor responses [25][26][27] dependent on extracellular calcium influx into vascular smooth muscle cells. 28 In agreement with this expectation, two DHP CCBs such as nifedipine and amlodipine, 29,30 as well as the unrelated phenylalkylamine derivative verapamil, 29 were able to reduce postural vasoconstriction at the dorsum of the foot 24,31 (Figure 3), a result in agreement with several other reports [32][33][34] (Table 1). Attenuation of postural vasoconstriction was probably the result of 35 Furthermore, non-CCB vasodilators, such as doxazosin, losartan and captopril (Figure 3), left postural vasoconstriction undisturbed in spite of a degree of microvascular dilation comparable to that induced by calcium channel blocking drugs.…”
Section: Ccbs Antagonise Postural Vasoconstrictionsupporting
confidence: 83%
“…Attenuation of postural vasoconstriction was probably the result of 35 Furthermore, non-CCB vasodilators, such as doxazosin, losartan and captopril (Figure 3), left postural vasoconstriction undisturbed in spite of a degree of microvascular dilation comparable to that induced by calcium channel blocking drugs. 24,31 In particular, doxazosin, an ␣ 1 -adrenoceptor blocker 36 ( Figure 3), did not modify the postural vasoconstrictor responses of skin blood flow. The data confirmed the independence from ␣-adrenergic vasoconstriction of cutaneous autoregulation at the dorsum of the foot, a site representative of nutritive capillary perfusion.…”
Section: Ccbs Antagonise Postural Vasoconstrictionmentioning
confidence: 89%
See 1 more Smart Citation
“…6 We have recently shown impaired postural skin blood flow control in patients with essential hypertension who were treated with calcium channel blockers (CCBs). 7 This pharmacological effect may contribute to ankle and/or pretibial edema in the absence of fluid retention, 8 a frequent, bothersome, and still not completely understood collateral effect of calcium antagonist drugs. 9 To test this hypothesis, we evaluated the relation between changes in postural skin vasomotion and objective measures of ankle swelling during treatment with graded doses of amlodipine, a dihydropyridine CCB.…”
mentioning
confidence: 99%
“…Verapamil increases plasma volume, 15 and it blunts postural cutaneous vasoconstriction in the lower extremities, as do amlodipine and nifedipine. 49 One placebo controlled study found that the prevalence of edema in patients with hypertension who were treated with verapamil was 3% compared with 5% in the placebo group. 50 Other non-placebo-controlled studies have found a 1% to 14% frequency of edema in subjects treated with verapamil.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%